Integrated Islamic Classroom Management and its Impact on Improving the Quality of Education in Islamic Schools - Feviasari, Heni; Melly Nuryani; Ikah Rohilah; Ade Budiansyah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
The research investigates the impact of integrated Islamic classroom management on improving the quality of education in Islamic schools. The primary purpose of this study is to explore how a combination of academic discipline and Islamic values in classroom management contributes to student engagement and character development. This qualitative research applies a case study approach, focusing on one Islamic school, SMPS IT Al Ishlah Cibinong, using interviews, observations, and documentation for data collection. The results demonstrate that integrating Islamic values such as honesty, responsibility, and discipline into the classroom has significantly enhanced student behavior and motivation, while also fostering a more conducive learning environment. Furthermore, the study reveals that the synergy between the national curriculum and Islamic teachings creates a holistic educational experience, supporting both academic achievement and spiritual development. Although the research identifies challenges, such as balancing strict discipline with flexibility in nurturing student character, it highlights the significant positive impact of this integrated approach. The study contributes to the field by providing a clearer understanding of how Islamic classroom management can be applied effectively, suggesting that further teacher training and consistent implementation are necessary to overcome challenges. This research offers practical insights for educators seeking to harmonize academic and spiritual education in Islamic schools, ensuring comprehensive student growth.